Հնչակեան քսան կախաղաններու քաղաքական գնահատականը - Եղիկ Ճէրճէրեան (ՀՀ ԳԱԱ հրատ.)
Враждебные отношения между социал-демократической партией Гнчакян (СДПГ) и партией Иттихат ве теракки начались в 1895 г. Главной причиной этого явилась идеология «османизма», проводимая Иттихатом. The hostile relations between the Socialist Democratic Henchak (SDHP) and Ittihad Ve Terakke (CUP) Parties began in 1895 and continued after the declaration of the 1908 Constitution, when SDHP became an opposition party.
Keywords: History; Armenian Genocide (1915); D History